Applying Psychological Theories to Promote Long-Term Maintenance of Health Behaviors. (November 2016) - Joseph, Rodney P.; Daniel, Casey L.; Thind, Herpreet; Benitez, Tanya J.; Pekmezi, Dori
Behavioral health theory provides a framework for researchers to design, implement, and evaluate the effects of health promotion programs. However, limited research has examined theories used in interventions to promote long-term maintenance of health behaviors. The purpose of this review was to evaluate the available literature and identify prominent behavioral health theories used in intervention research to promote maintenance of health behaviors. We reviewed theories used in intervention research assessing long-term maintenance (≥6 months postintervention) of physical activity, weight loss, and smoking cessation. Five prominent behavioral theories were referenced by the 34 studies included in the review: self-determination theory, theory of planned behavior, social cognitive theory, transtheoretical model, and social ecological model. Descriptions and examples of applications of these theories are provided. Implications for future research are discussed.